Hypersonic and Supersonic Flight Advances in Aerodynamics, Materials, and Vehicle Design - Volkov, Konstantin (IntechOpen, 2023)
Hypersonic flight vehicles have the potential to enable a range of future aviation and space missions. However, the extreme environmental conditions associated with high Mach number flight pose a major challenge for vehicle aerodynamics, materials and structures, and flight control, particularly within the hybrid ramjet/scramjet/rocket propulsion systems. The complexity of hypersonic vehicles requires closer coupling of aerodynamics and design principles with new materials development to achieve expanded levels of performance and structural durability. This book focuses on the fundamental disciplines and practical applications involved in the investigation, description, and analysis of super- and hypersonic aircraft flight including applied aerodynamics, aircraft propulsion, materials, and other topics.